A critique of effectiveness concept for heat exchangers; theoretical-experimental study. (October 2020) - Yan, Shu-Rong; Moria, Hazim; Pourhedayat, Samira; Hashemian, Mehran; Asaadi, Soheil; Sadighi Dizaji, Hamed; Jermsittiparsert, Kittisak
Highlights: A critique viewpoint is provided fro effectiveness. Experiments are carried out to support the said viewpoint. All possible curve behaviors of effectiveness are described. Probable previous imperfect effectiveness analysis was mentioned. Abstract: In this study attempts are made to clarify some hidden features of effectiveness concept (the ratio of actual heat transfer to maximum possible heat transfer) of heat exchangers and provide a critique viewpoint and comprehensive description about that. It is shown in present paper that the effectiveness parameter requires much more attention when it is used in fluid-flow parametric or sensitivity studies of heat exchangers and lack of consideration of its hidden features may lead to incorrect or imperfect decision-makings on curve behavior of effectiveness. Indeed, it is shown that the curve trend of effectiveness against the Reynolds number of one side of heat exchanger can be ascending, descending, or ascending-descending depending on the mass flow rate ( Re number) of the other side fluid. Although this critique viewpoint is not considered as a weakness of the effectiveness definition for heat exchangers, inattention may lead to wrong or imperfect inferences in sensitivity analysis of effectiveness parameter. Moreover, it is not logical to provide empirical correlation for effectiveness against flow parameters without the consideration of described features of effectiveness in this study. In order to support the described viewpoint some experiments are performed on double helical tube heat exchanger to evaluate the related thermal parameters and describe the mentioned features of effectiveness statistically. However, the provided analysis is valid for any other type heat exchanger as well.